2022
DOI: 10.3390/nu14245362
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Response to Intravenous Glucose Injection during Hemodialysis with Assessment of Entropy Alterations

Abstract: Background: The quality of autonomic blood pressure (BP) control can be assessed by the entropy of serial BP data. The aim of this study was to evaluate the effect of hemodialysis (HD) and glucose infusion (GI) on amplitude aware permutation entropy (AAPE) of hemodynamic variables during HD in chronic kidney disease patients with and without type-2 diabetes mellitus (DM). Methods: Twenty-one patients without DM (NDO) and ten with DM were studied. Thirty minutes after the start of HD, a 40% glucose solution was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The increase in pulse pressure in this study is also indicative of increased stroke volume ( Figure 3 ). A more detailed analysis of the hemodynamic effects of hypertonic glucose is presented in the companion publications of the same journal [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in pulse pressure in this study is also indicative of increased stroke volume ( Figure 3 ). A more detailed analysis of the hemodynamic effects of hypertonic glucose is presented in the companion publications of the same journal [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The time course and the magnitude of the perturbation was comparable to that of an intravenous glucose tolerance test, but it was completed during hemodialysis. This perturbation not only has metabolic effects that were analyzed and discussed previously but also the significant hemodynamic and blood volume effects analyzed and discussed in this article and in companion papers published in the same journal [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 91%
“…In our study, we found that the glucose infusion during HD in patients with HR < 60 at T -30 prevented a potential fall in DBP after one hour of the glucose infusion. It may be especially important for those with HR < 60 bpm, where the compensatory mechanisms of blood pressure control connected with HR variability may be impaired [ 19 ]. Moreover, we observed that patients with diabetes had lower DBP throughout the whole treatment session compared to those without diabetes ( p = 0.028).…”
Section: Discussionmentioning
confidence: 99%
“…Their study showed that AAPE, which takes into account the mean and difference of the sample amplitudes, is more sensitive to the signal’s amplitude characteristics than PE, and is a powerful tool for segmenting signals and detecting spikes. At present, AAPE has been used for image classification [ 37 ], feature extraction [ 38 , 39 , 40 ], and has been widely used in the mechanical field, especially in rotating machinery fault diagnosis [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%